Adaptation of the Marihuana Subscale of the Drug Use Resistance Self-Efficacy (DURSE) Scale in Adolescents - Olivo Chang, David Pascual (2021)
Background: self-efficacy is an important factor in drug use and there is a need for adapting psychological measuring instruments to the Peruvian context. The Drug Use Resistance Self-Efficacy (DURSE) scale (Carpenter, 2006) is a useful instrument for measuring this construct across different social situations. Objectives: to assess the psychometric properties of validity and reliability of the DURSE marijuana subscale among public school students from Lima. Method: the scale was translated and subjected to a pilot study consisting of 83 adolescents. The final version was administered to a sample of 1015 high school students. Results: the confirmatory factor analysis showed a one-factor structure with good fit indices (CFI = .990, TLI = .986, RMSEA = .057, SRMR = .015) and a high reliability coefficient (.98). The invariance was analyzed considering the participants’ sex, thus finding scalar but not metric invariance. Higher levels of selfefficacy were found among students who had not used marijuana, had no intention of trying it and refused marijuana offers. Conclusions: the DURSE marijuana subscale is a suitable instrument to measure marijuana use resistance self-efficacy among adolescents from Lima. Authorship contribution DPOC: study design, data analysis, preparation of the discussion and final revision of the manuscript. manuscript. CCPA: conception, design and supervision of the study, review of the discussion and conclusions. FOC: study design, review of data analysis, final revision of the manuscript. SMRS: study design, supervision of methodological procedures and invariance analysis.